Naukowość coachingu. Zarys problematyki = The Problem of Scientific Nature of Coaching: An Overview of the Issues - Bylica, Piotr (1976- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to indicate the key questions that, if addressed, could allow for an assessment of the scientific nature of coaching. This objective is achieved by 1) presenting the main issues and positions in the field of philosophy and general methodology of science related to disputes about the demarcation criterion and the characteristics of science and scientific knowledge, 2) pointing out the possibilities of relating these issues and positions to the assessment of how these characteristics or criteria are or are not fulfilled in the case of coaching.
Keywords: coaching; nauka; naukowość; spór o kryterium demarkacji; science; scientific nature; demarcation criterion debate